Can Machine Learning Models Predict Asparaginase-associated Pancreatitis in Childhood Acute Lymphoblastic Leukemia - Nielsen, Rikke L; Wolthers, Benjamin O; Helenius, Marianne; Albertsen, Birgitte K; Clemmensen, Line; Nielsen, Kasper; Kanerva, Jukka; Niinimäki, Riitta; Frandsen, Thomas L; Attarbaschi, Andishe; Barzilai, Shlomit; Colombini, Antonella; et al. (Journal of pediatric hematology/oncology, 2022)
Asparaginase-associated pancreatitis (AAP) frequently affects children treated for acute lymphoblastic leukemia (ALL) causing severe acute and persisting complications. Known risk factors such as asparaginase dosing, older age and single nucleotide polymorphisms (SNPs) have insufficient odds ratios to allow personalized asparaginase therapy. In this study, we explored machine learning strategies for prediction of individual AAP risk. We integrated information on age, sex, and SNPs based on Illumina Omni2.5exome-8 arrays of patients with childhood ALL (N=1564, 244 with AAP 1.0 to 17.9 yo) from 10 international ALL consortia into machine learning models including regression, random forest, AdaBoost and artificial neural networks. A model with only age and sex had area under the receiver operating characteristic curve (ROC-AUC) of 0.62. Inclusion of 6 pancreatitis candidate gene SNPs or 4 validated pancreatitis SNPs boosted ROC-AUC somewhat (0.67) while 30 SNPs, identified through our AAP genome-wide association study cohort, boosted performance (0.80). Most predictive features included rs10273639 (PRSS1-PRSS2), rs10436957 (CTRC), rs13228878 (PRSS1/PRSS2), rs1505495 (GALNTL6), rs4655107 (EPHB2) and age (1 to 7 y). Second AAP following asparaginase re-exposure was predicted with ROC-AUC: 0.65. The machine learning models assist individual-level risk assessment of AAP for future prevention trials, and may legitimize asparaginase re-exposure when AAP risk is predicted to be low.
Keywords: akutní lymfatická leukemie; Machine Learning; lidé; strojové učení; Precursor Cell Lymphoblastic Leukemia-Lymphoma; protinádorové látky; pankreatitida; Genome-Wide Association Study; dítě; Child; Asparaginase; Humans; Pancreatitis; asparaginasa; Antineoplastic Agents; celogenomová asociační studie